Acquisition of resistance to vemurafenib leads to interleukin‐10 production through an aberrant activation of Akt in a melanoma cell line. Issue 12 (17th September 2018) - Inozume, Takashi; Tsunoda, Toshiyuki; Morisaki, Takashi; Harada, Kazutoshi; Shirasawa, Seiji; Kawamura, Tatsuyoshi
Abstract: Serine/threonine‐protein kinase B‐Raf (BRAF) inhibitors are very effective in treating melanoma with BRAF mutations. BRAF inhibitors suppress aberrant growth of melanoma cells caused by BRAF mutations. BRAF mutations reportedly result in melanoma cells releasing immunosuppressive factors, and BRAF inhibitors elicit anti‐melanoma immune responses by reducing such factors. However, immunological characteristics of tumor cells that acquire resistance to BRAF inhibitors remain unknown. Here, we compared immunological characteristics between a melanoma cell line and its vemurafenib‐resistant subline. No differences were observed in the status of BRAF mutations, expression of surface molecules related to antitumor T‐cell responses or recognition by human leukocyte antigen‐A*0201‐matched melanoma‐specific cytotoxic T lymphocytes in a short‐term co‐culture assay. However, resistant tumor cells released high amounts of interleukin‐10 depending on aberrant activation of Akt signaling, and dendritic cell functions were considerably suppressed by culture supernatants of the resistant cells. Our findings demonstrated a novel immunological mechanism contributing to tumor growth owing to drug resistance to BRAF inhibitors.